Prevalence and factors associated with frailty among older Indian adults with cancer: A single-center cross-sectional analytical study from a geriatric oncology clinic in India - Abhijith R Rao; Vanita Noronha; Anant Ramaswamy; Anita Kumar; Anupa Pillai; Arshiya Sehgal; Sharath Kumar; Shreya C Gattani; Renita Castelino; Ratan Dhekale; Sarika G Mahajan; Anuradha A Daptardar; et al. (Cancer Research, Statistics, and Treatment, 2023)
Background: Frailty is a significant concern in older patients with cancer, yet there are limited data on frailty and its associated risk factors, particularly in Indian patients. Objectives: The primary objective was to evaluate the occurrence of frailty among older Indian patients with cancer. The secondary objective was to identify the factors associated with frailty. Materials and Methods: This cross-sectional study was conducted in the geriatric oncology clinic of the Department of Medical Oncology at the Tata Memorial Hospital, Mumbai, India. We included all patients evaluated between February 2020 and June 2023. Frailty was defined using the clinical frailty scale (CFS) score ≥4. The bivariate association between frailty and other factors was assessed by the Chi-square test and multivariate logistic regression. Results: We included 2214 patients, with a median age of 67 (interquartile range [IQR], 64–72) years, and 1708 (77.2%) were male. The most common cancer sites were gastrointestinal (815 [37.1%]) and lung (786 [35.8%]). We found that 1324 (59.8%) patients were frail. Frailty was positively associated with age (adjusted odds ratio [aOR], 1.62; 95% confidence interval [CI], 1.15-2.29), Eastern Cooperative Oncology Group performance status (ECOG PS) (PS 1: aOR, 4.75; 95% CI, 1.45-15.59; PS 2: aOR: 10.11; 95% CI, 2.98-34.25; PS 3: aOR, 10.97; 95% CI 2.49-48.23), tumor metastasis (aOR, 1.62; 95% CI, 1.26-2.09), impaired basic activities of daily living (aOR, 1.84; 95% CI, 1.20-2.83), impaired instrumental activities of daily living (aOR, 4.21; 95% CI, 2.94-6.02), higher timed-up-and-go score (aOR, 3.26; 95% CI, 2.54-4.18), at risk for malnutrition (aOR, 2.05; 95% CI, 1.52-2.75), malnutrition (aOR, 2.33; 95% CI, 1.50-3.61), depression (aOR, 2.22; 95% CI, 1.66-2.96), and hypoalbuminemia (aOR, 0.59; 95% CI, 0.45-0.79). Conclusion: Frailty is prevalent among older Indian patients with cancer. CFS may be considered a rapid screening tool to help identify vulnerable patients in need of a geriatric assessment (GA). These findings emphasize the need for a multidisciplinary GA and targeted interventions to address frailty and improve outcomes in this vulnerable population. (Clinical Trials Registry-India: CTRI/2020/04/024675).